2018
DOI: 10.1111/apha.13056
|View full text |Cite
|
Sign up to set email alerts
|

Regional regulation of focal adhesion kinase after concentric and eccentric loading is related to remodelling of human skeletal muscle

Abstract: Focal adhesion kinase phosphorylation was greater at 8 weeks after ECC RT and was muscle region-specific. FAK activity correlated to contraction-dependent architectural remodelling, suggesting a potential role of FAK in orienting muscle structural changes in response to distinct mechanical stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 64 publications
5
69
0
Order By: Relevance
“…Likewise, they reported that the content of activated costamere‐associated proteins increased more prominently at the distal site. This phenomenon, as suggested by the authors, may indicate a potential to preferentially increase the amount of myofibril Z‐bands in series (thus reflecting an FL increase) at the distal portion of the muscles (Franchi, Ruoss, et al, ). Although stretch training seems to elicit different responses at different sites along the muscle (Simpson et al, ), fascicle elongation also may be a consequence of decreases in stiffness of the connective tissue, particularly the perimysium, which is the largest extracellular contributor of tissue stiffness (Akagi & Takahashi, ; Purslow, ).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Likewise, they reported that the content of activated costamere‐associated proteins increased more prominently at the distal site. This phenomenon, as suggested by the authors, may indicate a potential to preferentially increase the amount of myofibril Z‐bands in series (thus reflecting an FL increase) at the distal portion of the muscles (Franchi, Ruoss, et al, ). Although stretch training seems to elicit different responses at different sites along the muscle (Simpson et al, ), fascicle elongation also may be a consequence of decreases in stiffness of the connective tissue, particularly the perimysium, which is the largest extracellular contributor of tissue stiffness (Akagi & Takahashi, ; Purslow, ).…”
Section: Discussionmentioning
confidence: 70%
“…Despite the observed beneficial effects of stretch training on FL, the findings are not necessarily due to an increase in muscle fibre length. After eccentric training, Franchi et al (); Franchi, Ruoss, et al () observed higher growth in vastus lateralis cross‐sectional area at the distal site compared with the muscle belly. Likewise, they reported that the content of activated costamere‐associated proteins increased more prominently at the distal site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Manuscripts from 2018 indicate how much attention very young manuscripts are receiving . Listed here are less than half of the original articles receiving double‐digit citations.…”
mentioning
confidence: 99%